Application of bifunctional catalysts and metal organic frameworks in metal air batteries for renewable power conversion applications. (2021) - Kumar, Prakash; Goyal, Sunil Kumar; Singh, Bhuwan Pratap
Abstract: This paper presents the development of dynamic and stable metal air batteries (MABs) for power storage and renewable power conversion (RPC) applications. Presented power storage unit (PSU) and RPC, such as fuel cell, is based on oxygen reduction reaction (ORR). Such PSUs are associated with poor kinetic ORR and oxygen evolution reaction (OER) limitations. Stable and dynamic catalysts like single atom catalysts, metal-free carbon materials and nanocomposites has renovated its applications in RPC. Recent development of bifunctional catalysts (BFC) and metal organic frameworks (MOFs) for both OER and ORR has improved the stability of MABs. For the development of BFCs strategies being carried out includes micro-nano design (e.g., chemical vapor deposition, electrochemical methods, template methods and hydrothermal methods), fabrication of new materials (composite materials, transition-metal materials, and carbon), and material property alteration (oxygen defects, heteroatom doping, interfacial strain, adjustments of electronic structures, nano composites, metal–oxygen bonds, etc.). For the fabrication of MOFs, aqueous and non-aqueous electrolytes are being developed. This paper deals with brief discussion of MABs for active and stable application in PSUs and RPCs.